Glenohumeral Translations in Overhead Workers with Sub-Acromial Impingement Syndrome: A Review - Shinde, Sandeep B.; Dalvi, Shivanee K.; Shinde, Ravindra V. (International Journal of Occupational Safety and Health, 2023)
Introduction: The third most common musculoskeletal condition is shoulder pain with a prevalence of up to 70%. The second most frequent shoulder condition is subacromial impingement syndrome. Impingement can be classified as either anterosuperior or posterosuperior. Faulty posture, altered scapular or glenohumeral kinematics, posterior capsular tightness, and acromial or coracoacromial arch pathology are all potential extrinsic mechanics that can lead to Subacromial impingement syndrome. The purpose of this review is to find the different variation in translation that takes place in the glenohumeral joint in Subacromial impingement syndrome in overhead workers. Methods: We performed a review of the various translations observed in the glenohumeral joint in subacromial impingement syndrome and discussed the evidence-based studies. For the review, an electronic search for relevant articles using PUBMED, Pedro, Research Gate, and Google Scholar databases up to Dec 2022 was done wherein MeSH search terms and free words were used. Articles underwent the selection process and were selected on the basis of inclusion criteria. Articles were selected based on the author's expertise, self-knowledge and reflective practice. Results: The current study included 11 articles that fulfilled the inclusion criteria suggesting that various humeral translations in overhead workers. The above-reviewed studies provided evidence that based on occupational demands abnormal variations occur. Conclusion: This review has provided an overview of the previous and recent literature on humeral head translation seen in sub-acromial impingement. This study concludes that superior translation is more common as compared to anterior-superior translation and posterior-superior translation.